Contextual Changes and Shifts in Pedagogical Paradigms: Post-COVID-19 Blended Learning as a Negotiation Space in Teacher Education - Liat Biberman-Shalev; Orit Broza; Nurit Chamo (MDPI AG, 2023)
This study investigates a post-COVID-19 curricular change in the blended learning (BL) academic timetable of a teacher education college where, pre-COVID-19, most academic courses were taught face-to-face (F2F) on campus. At present, the meetings are F2F for three weeks, followed by a week of remote learning, combining synchronous and asynchronous pedagogies. This study explores these two aspects of the online component and the considerations for their implementation. In a mixed-method approach, the data were collected using a closed questionnaire and two focus groups involving 76 lecturers and 553 students altogether. Of the wide range of pedagogies identified, the highest success rating was accorded to synchronous frontal lectures via Zoom by the students and to integrating MOOCs, YouTube, and Podcasts by the lecturers. Moreover, compared to the lecturers, the students rated the success of asynchronous self-directed learning considerably higher. Qualitative analysis revealed that pedagogies slated for the online module were frequently negotiated between students and teachers. Findings suggest that a structural change in the curriculum could be a first step in rethinking pedagogies in the post-COVID-19 education arena. The next step should focus on narrowing the gap between lecturers' and students' perceptions regarding the success of the various pedagogies.